Myrtle improves renovascular hypertension-induced oxidative damage in heart, kidney, and aortic tissue - ŞEN, ALİ; ŞENER, GÖKSEL; AKBAY, TUĞBA (My University, 2022)
Renovascular hypertension is defined as the reduction in renal perfusion resulting in sustained hypertension. This study aims to investigate the possible effects of myrtle leaf extract (Myrtus communis L.) on, heart, kidney and aorta tissues in the experimental renovascular hypertension (RVH). 32 male Wistar Albino rats were divided into four groups as control, hypertension, hypertension+ramipril, and hypertension+myrtle leaf extract treatment groups. RVH model was induced by Goldblatt\"s 2-kidney 1-clip method. 12 weeks later than the treatment blood pressures were recorded and oxidant and antioxidant parameters, tissue factor activity, and histological analysis were determined in the kidney, heart, and aortic tissues. The blood pressure levels of the hypertension group significantly increased compared to the control group. Administration of myrtle leaf extract and ramipril significantly decreased the increased blood pressure. In the hypertension group, oxidative damage increased in the kidney, heart, and aorta tissues. In the histological evaluation of tissues in RVH, heart muscle fibres degenerated. Bowman capsule and glomeruli dilated and tubules damaged in the kidney. Myrtle leaf extract administration regenerated the damages and degenerations. The administration of myrtle leaf extract restored the impaired oxidant-antioxidant balance in the heart, kidney and aorta tissues of hypertensive rats. Myrtle leaf extract can be considered as an alternative antihypertensive treatment target in the prevention of oxidative stress-induced damage in renovascular hypertension.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Tıbbi Biyoloji; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Biochemistry; Medical Biology; Life Sciences; Natural Sciences; BİYOLOJİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); BIOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); Biochemistry (medical); Renovascular hypertension; Myrtus communis L; Myrtle leaf extract; Oxidative stress; PHENOLIC-COMPOUNDS; BLOOD-PRESSURE; COMMUNIS; STRESS; ANTIOXIDANT; LEAVES; PATHOPHYSIOLOGY; IDENTIFICATION